Поселення трипільської культури Тополі - Пересунчак, О.С. (Материалы по археологии Северного Причерноморья, 2015)
The article is dedicated to the new settlement of Trypillian culture named Topoli which was discovered by author in 2003. It is located in the neighbourhood of eponymous village in the area of Gaivoron district, Kirovograd region. There are some characteristic features of the geographical position of the site and a notable amount of artefacts that have being found during the visual investigations since the period of discovering till 2014. The article describes the varieties of pottery, lithic equipment and the other artefacts dated by the period of Aeneolithic. Special attention is paid to the discovery of the fragmented tool made of jade. On the basis of pottery complex the author dates it to the stage BI of Trypillian culture, more precisely to its early stage.